2020
DOI: 10.1016/j.isci.2020.101338
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochromes Suppress HIF1α in Muscles

Abstract: Summary Muscles preferentially utilize glycolytic or oxidative metabolism depending on the intensity of physical activity. Transcripts required for carbohydrate and lipid metabolism undergo circadian oscillations of expression in muscles, and both exercise capacity and the metabolic response to exercise are influenced by time of day. The circadian repressors CRY1 and CRY2 repress peroxisome proliferator-activated receptor delta (PPARδ), a major driver of oxidative metabolism and exercise endurance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…In contrast to our finding that maximum sprint speed is indistinguishable between ZT13 and ZT21 in sedentary animals, male mice robustly increased their maximum sprint capacity in a striking time of day dependent manner after six weeks of running wheel training. As we 32 and others 54 have seen in prior studies, female mice tend to be more active than males; in addition, both maximum speed and tissue glycogen content are significantly greater in trained c57BL/6J female mice than they are in males. The explanation for this robust sexual dimorphism is unclear 54 .…”
Section: Discussionsupporting
confidence: 66%
“…In contrast to our finding that maximum sprint speed is indistinguishable between ZT13 and ZT21 in sedentary animals, male mice robustly increased their maximum sprint capacity in a striking time of day dependent manner after six weeks of running wheel training. As we 32 and others 54 have seen in prior studies, female mice tend to be more active than males; in addition, both maximum speed and tissue glycogen content are significantly greater in trained c57BL/6J female mice than they are in males. The explanation for this robust sexual dimorphism is unclear 54 .…”
Section: Discussionsupporting
confidence: 66%
“…Only recently, CRY1, but not CRY2, was identified as a negative regulator of HIF-1α in the mouse fibroblast NIH3-T3 and MEF cell lines, at the level of transactivation capacity, as well as at the level of protein quantity (Dimova et al 2019). Furthermore, CRY1 and CRY2 are reported to suppress HIF1α-BMAL1 heterodimers in mouse muscles (Vaughan et al 2020). Against this background, the contemporaneously increased quantities of CRY1 and HIF-1α protein over the period of 2 h after the 6 h tNMR treatment seem astonishing (Figure 5B and D).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of hypoxia-regulated transcripts can enhance cell survival under stressful conditions and contribute to tumorigenesis (Choudhry and Harris, 2018; Semenza, 2013, 2017). We and others recently demonstrated that CRY1 and CRY2 suppress both the protein accumulation and transcriptional activation of HIF1α and HIF2α(Dimova et al, 2019; Vaughan, 2020). HIFs are closely related to CLOCK and BMAL1 (Fribourgh and Partch, 2017) and we and others have shown that BMAL1 dimerizes with HIF1α (Hogenesch et al, 1998; Vaughan, 2020; Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We and others recently demonstrated that CRY1 and CRY2 suppress both the protein accumulation and transcriptional activation of HIF1α and HIF2α(Dimova et al, 2019; Vaughan, 2020). HIFs are closely related to CLOCK and BMAL1 (Fribourgh and Partch, 2017) and we and others have shown that BMAL1 dimerizes with HIF1α (Hogenesch et al, 1998; Vaughan, 2020; Wu et al, 2017). Given that the CRY2 D325H mutation reduces its association with and repression of CLOCK:BMAL1, it may also influence repression of HIF1α/BMAL1 by altering protein-protein interactions, although it is unclear whether the interaction of CRYs with HIFs involves the secondary pocket.…”
Section: Discussionmentioning
confidence: 99%